EXTRACTION OF THIACLOPRID FROM HONEY USING AQUEOUS BIPHASIC SYSTEMS BASED ON POTASSIUM PHOSPHATE AND IONIC LIQUIDS - Maric, Aleksandar; Jovanov, Pavle; Sakač, Marijana; Radić, Bojana; Đermanović, Branislava; Gadžurić, Slobodan (Food and Feed Research, 2024)
Thiacloprid, a widely used neonicotinoid pesticide, poses a significant health risk when present in honey. Conventional extraction techniques are often complex and time-consuming, highlighting the need for more efficient methods. This study investigated the application of aqueous biphasic systems (ABS) based on ionic liquids (ILs) in combination with the kosmotropic salt potassium phosphate (K₃PO₄) for extracting thiacloprid from honey, intending to enhance extraction efficiency and simplify the process. Two commercially available ionic liquids, 1-butyl-3-methylimidazolium chloride ([C4mim][Cl]) and tetrabutylammonium chloride ([N4444][Cl]), were assessed for their phase-forming properties and extraction efficiencies. Both systems achieved extraction efficiencies exceeding 90%, with the [C4mim][Cl] system demonstrating superior performance, attaining an extraction efficiency (EE%) of 98.11 ± 1.26%. Additionally, spectrophotometric detection was applied, providing a faster, simpler, and more cost-effective alternative to chromatographic methods. The results underscore the potential of IL-based ABS systems with K₃PO₄ as a sustainable and effective alternative to traditional extraction methods, demonstrating a selective, rapid, and environmentally friendly approach for extracting thiacloprid from a complex matrix such as honey.
Keywords: honey; thiacloprid; ionic liquids; aqueous biphasic systems